Dominance Conditions for Multivariate Utility Functions - Scarsini, Marco (Management Science, 1988)
Stochastic dominance conditions are given for n-variate utility functions, when k-variate risk aversion is assumed for k = 1, 2, …, n. These conditions are expressed through a comparison of distribution functions, as in the well-known univariate case, and through a comparison of random variables defined on the same probability space.